Design and Exploratory Neuropharmacological Evaluation of Novel Thyrotropin-Releasing Hormone Analogs and Their Brain-Targeting Bioprecursor Prodrugs - Laszlo Prokai; Krisztina Konya; Szabolcs Szarka; Katalin Prokai-Tatrai; Vien Nguyen (Pharmaceutics, 2013)
Efforts to take advantage of the beneficial activities of thyrotropin-releasing hormone (TRH) in the brain are hampered by its poor metabolic stability and lack of adequate central nervous system bioavailability. We report here novel and metabolically stable analogs that we derived from TRH by replacing its amino-terminal pyroglutamyl (pGlu) residue with pyridinium-containing moieties. Exploratory studies have shown that the resultant compounds were successfully delivered into the mouse brain after systemic administration via their bioprecursor prodrugs, where they manifested neuropharmacological responses characteristic of the endogenous parent peptide. On the other hand, the loss of potency compared to TRH in a model testing antidepressant-like effect with a simultaneous preservation of analeptic activity has been observed, when pGlu was replaced with trigonelloyl residue. This finding may indicate an opportunity for designing TRH analogs with potential selectivity towards cholinergic effects.